Initial computed tomography features of known inpatient ward versus intensive care admission COVID-19 cases: is there any difference? - Unal, Ozlem; Koç, Ural; Özkan, Erdem; Hasanoğlu, İmran; Surel, Aziz Ahmet; Güner, Rahmet (The European Research Journal, 2022)
Objectives: The aim of this study was to evaluate initial computed tomography (CT), basic clinical and demographic features of cases with COVID-19 pneumonia with known inpatient ward and intensive care unit hospitalization. Methods: A total of 200 cases (103 males, 97 females; age range: 18-92 years) were retrospectively and randomly collected whom were hospitalized and followed up at infectious disease inpatient ward and intensive care unit (ICU). The initial CT findings were interpreted by two radiologists at the same session by consensus. Results: Cough (61%) and fever (54%) were the main symptoms at the onset presentation. Initial chest CT imaging revealed that 79.5% ground-glass opacities. Bilateral distribution (62.5%), peripheral and central distribution (45.5%), dorsal and ventral involvement (52.5%) were identified in all cases. CT features predominantly were at right and left lower lobes (69.5%, 62.5%; respectively). Cases with known ICU admission had statistically significant differences with inpatient ward admission cases in regards to CT features included mixed GGO and consolidation, bronchial wall thickening, pleural effusion, subpleural band, emphysema, coronary calcification, cardiothoracic ratio, aorta diameter. Conclusions: Initial CT features may be helpful for foreseeing admission to ICU as in clinical features.